Associations of Haplotypes Upstream of IRS1 with Insulin Resistance, Type 2 Diabetes, Dyslipidemia, Preclinical Atherosclerosis, and Skeletal Muscle LOC646736 mRNA Levels - Selma M. Soyal (Journal of Diabetes Research, 2015)
The genomic region ~500 kb upstream of IRS1 has been implicated in insulin resistance, type 2 diabetes, adverse lipid profile, and cardiovascular risk. To gain further insight into this chromosomal region, we typed four SNPs in a cross-sectional cohort and subjects with type 2 diabetes recruited from the same geographic region. From 16 possible haplotypes, 6 haplotypes with frequencies >0.01 were observed. We identified one haplotype that was protective against insulin resistance (determined by HOMA-IR and fasting plasma insulin levels), type 2 diabetes, an adverse lipid profile, increased C-reactive protein, and asymptomatic atherosclerotic disease (assessed by intima media thickness of the common carotid arteries). BMI and total adipose tissue mass as well as visceral and subcutaneous adipose tissue mass did not differ between the reference and protective haplotypes. In 92 subjects, we observed an association of the protective haplotype with higher skeletal muscle mRNA levels of LOC646736, which is located in the same haplotype block as the informative SNPs and is mainly expressed in skeletal muscle, but only at very low levels in liver or adipose tissues. These data suggest a role for LOC646736 in human insulin resistance and warrant further studies on the functional effects of this locus.